Pendampingan Santri Berbudi Pekerti Baik Melalui Pembelajaran Kitab Taisirul Kholaq di Pondok Pesantren Alif Lam Mim - Elsa Tiara; Ayu Febriyanti; Aris Priyanto; Inayah Priyatun; Siti Salamah; Rifani Raniasati; Ana Chonitsa; Amma Chorida Adila; Adinda Riski Amalia; Muhammad Maskur Musa; Teguh Handoyo; Hendri Hermawan Adinugroho (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The current era of globalization has made life more modern. Humans are no longer difficult in carrying out life because of the increasingly rapid development of the times. But behind the benefits of this technological development, there is a phenomenon of moral degradation. That is a phenomenon where there is a decline in morals or morals in individuals or groups of people. . Therefore, it is necessary to learn how to be virtuous, one of which is through the book of Taisirul Kholaq. The purpose of this study is to increase understanding of the importance of applying good manners in daily life according to the study of the book of taisirul kholaq. Given that good character will create superior human beings who are able to overcome and face various challenges in the current era of globalization wisely. The method in this study is Bandongan, something that is often used in Islamic boarding schools, namely the students will learn by listening together about what is conveyed by the teacher. Based on mentoring activities with good character through learning the Taisirul Kholaq book at the Alif Lam Mim Islamic Boarding School, the students were able to evaluate themselves regarding their behavior. they can also improve their morals especially towards older people. From this learning, they are also more enthusiastic in living life because they are taught to always be grateful and accept their destiny or situation. Even though there were some obstacles in this activity such as limited time, the students were still enthusiastic so they could maximize their time efficiently.